2017
DOI: 10.1039/c6ra28455h
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared probes based on fluorinated Si-rhodamine for live cell imaging

Abstract: Si-rhodamine probe with a trifluoromethyl group on the 2-position of the pendant phenyl ring retains high brightness and excellent stability in a harsh physiological environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Another typical approach to avoid the ICT state formation is the introduction of cyclic substituents at the nitrogen atom . This approach was achieved in the design of a wide range of the fluorescent dyes , . Probably, the introduction of such small cycles impedes the changes of the angle between the C–N–C atoms in the amino group, which affects the formation of the ICT state .…”
Section: Resultsmentioning
confidence: 99%
“…Another typical approach to avoid the ICT state formation is the introduction of cyclic substituents at the nitrogen atom . This approach was achieved in the design of a wide range of the fluorescent dyes , . Probably, the introduction of such small cycles impedes the changes of the angle between the C–N–C atoms in the amino group, which affects the formation of the ICT state .…”
Section: Resultsmentioning
confidence: 99%
“…A fluorinated Si-rhodamine is observed to have redshifted absorption spectra over the nonfluorinated compounds [ 46 ]. In Scheme 7 , the Si-rhodamine is synthesized with a phenyl ring containing a trifluoromethyl substituent compared to a similar dye with a methyl substituent.…”
Section: Fluorinated Rhodamine Based Dyesmentioning
confidence: 99%
“…Table 2 highlights the bathochromic shifts presented by the different fluorinated rhodamine dyes. Some of the most popular modifications made to the rhodamine structure are the addition of alkyl groups to the nitrogen of rhodamine, most commonly adding an azetidine ring or fluorine-containing alkyl groups as seen in compounds 38 – 40 [ 42 , 43 , 46 ]. Fluorine atoms are also typically incorporated into the rhodamine structure on the carbon adjacent to the amino group like in compound 29 , or on the phenyl ring added by the phthalic anhydride precursor as shown in compound 48 or 50 .…”
Section: Fluorinated Rhodamine Based Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, after replacing the 10th oxygen atom of the xanthene moiety with a SiMe 2 group, a new class of NIR fluorophores (silicon-rhodamine, SiR) was developed. These highly permeable and biocompatible SiR probes are especially useful for bioimaging applications. However, these fluorescent rhodamines are cationic conjugated compounds, in which the nucleophilic attack on the ninth carbon atom of the xanthene occurs easily and induces drastic changes to the optical properties. , The replacement of the N,N-dimethyl amino groups of the classic rhodamine with four-membered azetidines or tert-alkylamino groups yields a new generation of rhodamine probe with a significant increase in brightness and photostability. , Stefan W. Hell and co-workers reported that the fluorinated silicon-rhodamines possess high photostability and high fluorescence quantum yields in water . Our previous work demonstrated that the Si-rhodamine dyes with a trifluoromethyl at the 2-position of the pendant phenyl ring retains high brightness and excellent stability . Here, we report the development of NIR emission Si-rhodamine dyes (SiRMO) with the methoxy groups in the ortho-position of the benzene moiety (Chart ).…”
mentioning
confidence: 99%